(untitled) (Medico Legal Update, 2020)
HIV/AIDS epidemic nowadays has become as global effects, even if the prevention efforts still goes to conducted and improved. The aim of research was to knowing the effect of snowball method toward family support role in PLWHA ARV adherence. The research method used is quasy experiment with pre-posttest one group only design with the purposive sampling technique. Research results showed from 20 respondents were found at Malawei Public Health Center of Sorong City was that there are differentiation of mean values between pre-postest are 8,09 and standard deviation values are -0,49 and the Wilcoxon statistical test results was that the p values equal to 0,000 which mean there is a significant effect of the snowball method toward family support role in PLWHA ART’s adherence. The snowball as the teaching method technique could be implemented in order to HIV/AID knowlege update and improves the PLWHA ART’s adherence.